Film Effectiveness Downstream the Trenches with Tilted Target Wall - Fan Yang; Mohammad E. Taslim (International Journal of Rotating Machinery)
Film cooling is a commonly-accepted effective way to protect the gas turbine hot sections from the high temperature products of the combustion chamber. Numerous film hole geometries have been the subject of investigation by many researchers over the past three decades with the aim of keeping the target wall under the maximum allowable temperature with the least amount of precious cooling air and minimum aerodynamic losses. In this study, we are proposing a new trench geometry that is fed by 30°-inclined embedded circular film holes entering from the trench sidewall. The cooling jets impinge on the opposite wall of the trench which is tilted towards the jets and then is pushed over the coverage wall by the main flow. Three trench geometries with the same exit area and tilt angles (the angle between the trench side- and top-wall) of 75°, 90°, and 105° degrees are tested for three blowing ratios of 0.5, 0.75, and 1.0, and the film effectiveness results are compared using the adiabatic pressure sensitive paint technique. CFD analyses are also performed using the realizable k−ε turbulence model with the enhanced wall function option. Major conclusions of this study were that the trench geometry with the trench tilt angle of 75°, corresponding to the smallest trench volume, had the best performance at the lowest blowing ratio, and good agreement was observed between the CFD and test results.